2017
DOI: 10.1007/s10853-017-1084-8
|View full text |Cite
|
Sign up to set email alerts
|

Highly transparent and conductive indium-doped zinc oxide films deposited at low substrate temperature by spray pyrolysis from water-based solutions

Abstract: In this paper, indium-doped zinc oxide (IZO) films were grown by spray pyrolysis, using zinc acetate and indium acetylacetonate precursors. The focus was on developing a solution recipe based on water as solvent, with only minor acetic acid content, as well as keeping the substrate temperature as low as possible-at 360°C. The process is therefore environment friendly and energy efficient. Despite the challenging conditions, the resulting IZO films were highly transparent and conductive. Their texture deviates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 28 publications
2
28
0
Order By: Relevance
“…A low HAc concentration resulted in unwanted precipitates on the film surface, while a high HAc concentration caused an increase in film resistivity. In accordance with our previous results [8], the lowest resistivity (7.4 × 10 −3 Ω·cm) combined with highest transparency (>80%) were obtained for~1500 nm-thick films deposited from a solution containing 8 vol % HAc (pH = 3.65).…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…A low HAc concentration resulted in unwanted precipitates on the film surface, while a high HAc concentration caused an increase in film resistivity. In accordance with our previous results [8], the lowest resistivity (7.4 × 10 −3 Ω·cm) combined with highest transparency (>80%) were obtained for~1500 nm-thick films deposited from a solution containing 8 vol % HAc (pH = 3.65).…”
Section: Resultssupporting
confidence: 92%
“…Within the narrow concentration range for InAc 3 (3-5 mol %) and HAc (4-16 vol %) in this study, there was practically no obvious influence on the growth rate, as shown in Figure 1a,b. In comparison to our previous study [8], changing the zinc acetate concentration from 0.1 to 0.2 M and the type of indium precursor salt resulted in a~4-fold increase of the growth rate, as displayed in Figure 1. In Figure 1c it can be observed that increasing the deposition temperature from 360 to 400 • C resulted in a minor gradual decrease of the growth rate.…”
Section: Film Growth Ratementioning
confidence: 42%
See 2 more Smart Citations
“…1.2 × 10 20 cm −3 although those films prepared from sputtering have somewhat higher values of these transport properties. In-doped ZnO (IZO) films deposited either by sputtering or spray pyrolysis have been investigated extensively [17][18][19][20][21][22][23][24][25][26] and the films produced by spray pyrolysis show conductivities of the order of 700 Ω −1 cm −1 and carrier concentrations around 3.2 × 10 20 cm −3 . We have investigated whether co-doping with both Si and In together can enable the spray deposition of films which reduce the In content whilst also maintaining the overall electrical and optical performance.…”
Section: Introductionmentioning
confidence: 99%